Billiardo: A Novel Virtual Coordinates Routing Protocol Based on Multiple Sinks for Wireless Sensor Network, ISSN /e-ISSN 0929-6212 / 1572-834X - Aksa Karima (Wireless Personal Communications, 2017)
Geographic routing protocols based on virtual coordinate system are used in wireless sensor networks without GPS assistance or any localization technique. They rely completely on virtual coordinates derived from relative distances or hop counting to a set of anchor nodes in the sensor network. Despite the fact that the recently proposed virtual coordinate protocols have gained advantages as they are GPS free, they suffer from crucial inevitable problems. The reason for such a case lies, in fact, on these protocols which depend widely on the characteristic of “fixed reference points” (called anchors). The worst of these engendered problems is that of the unique reference framework where it is quite difficult to assign the existing nodes a unique identity. This lack of uniqueness cannot guarantee delivery and fails most of the time to forward the packet successfully. Moreover, a question rises here on how to select the anchors in order to use them in the field of work. Therefore; this paper comes to find out another way to solve the above-mentioned problems. The proposed routing protocol “Billiardo” is of greedy type based on virtual coordinates system. Its key idea is to use more than one sink, and all these sinks are used as anchors to allow each sensor to get its virtual coordinates. This protocol depends on hops’ count to find the shortest path towards just one selected sink among the other sinks without any complicated formula. Through tested simulation Billiardo proves to be far better and more efficient than the others to avoid all the thwarting problems in forwarding the packet.